Perkembangan Motorik Halus Anak Usia Pra Sekolah 4-5 Tahun dengan Kegiatan Montase - I Made Sundayana; Kadek Yudi Aryawan; Putu Cyndy Fransisca; Ni Made Dwi Yunica Astriani (Jurnal Keperawatan Silampari, 2020)
The purpose of this study is to analyze the effect of montage activities on the fine motor development of pre-school aged children 4-5 years. The research method used was pre-experimental with one group pre and post test design. The results showed an average pre-test value was 43.44 and the post-test mean value was 68.21. Paired Sample T-test results obtained Ï-value (0,000) <Î± (0.05), there is the effect of montage activity on fine motor development in pre-school age children 4-5 years. Conclusion, fine motor is a limited movement of parts that include small muscles, especially movements of the fingers such as writing, drawing, and holding something. Keywords: Children 4-5 Years Old, Montage Activities, Fine Motor Development